2004
DOI: 10.1063/1.1664026
|View full text |Cite
|
Sign up to set email alerts
|

Formation and evolution of luminescent Si nanoclusters produced by thermal annealing of SiOx films

Abstract: Si nanoclusters embedded in SiO2 have been produced by thermal annealing of SiOx films prepared by plasma enhanced chemical vapor deposition. The structural properties of the system have been investigated by energy filtered transmission electron microscopy (EFTEM). EFTEM has evidenced the presence of a relevant contribution of amorphous nanostructures, not detectable by using the more conventional dark field transmission electron microscopy technique. By also taking into account this contribution, an accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
253
2
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 320 publications
(279 citation statements)
references
References 41 publications
21
253
2
3
Order By: Relevance
“…This is interesting, as the crystallization temperature of amorphous Si is known to be significantly lower (about 500 • C) [28]. High crystallization temperatures have been observed before in Si-ncls embedded in amorphous oxides [2,3] and it is tempting to attribute this effect to the influence of the surrounding amorphous oxide network. However, studies of isolated Si-ncls prepared by PECVD have also shown crystallization temperatures well above those typical in bulk a-Si [57].…”
Section: Structural Modelmentioning
confidence: 97%
See 4 more Smart Citations
“…This is interesting, as the crystallization temperature of amorphous Si is known to be significantly lower (about 500 • C) [28]. High crystallization temperatures have been observed before in Si-ncls embedded in amorphous oxides [2,3] and it is tempting to attribute this effect to the influence of the surrounding amorphous oxide network. However, studies of isolated Si-ncls prepared by PECVD have also shown crystallization temperatures well above those typical in bulk a-Si [57].…”
Section: Structural Modelmentioning
confidence: 97%
“…Previous [2,12,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and our own [21] studies have shown that the integral PL time decay in Si-based nanostructures can be fitted by the well-known stretched exponential function…”
Section: Optical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations